Organic chemistry - Fox, Marye Anne
Welcome to Organic Chemistry as you have never seen it before! Fox and Whitesell's Organic Chemistry, Second Edition represents a new way of learning which is based on the authors' experiences teaching undergraduate students at the University of Texas at Austin. No other book is organized and written like this text. The aim of its approach is to teach the student concepts that they will need to know for future course work, medical school, etc., rather than promoting tedious memorization. As a result, they will be better prepared for the future, and leave your class with a greater understanding of what makes organic chemistry such an important course